Widening international entrepreneurship research - María Ripollés Meliá; Andreu Blesa (MDPI, 2020)
Widening International Entrepreneurship Research addresses several unresolved questions and thus moves forward by acknowledging that future international entrepreneurship research needs to find new ways to further enrich its knowledge. The book presents the results of six studies that explain how human resource management contributes to the strategy of early internationalization, compares different experiences in several countries, assesses innovation in international entrepreneurship education teaching, analyses the effects of entrepreneurial education on entrepreneurial skills, and provides new knowledge about the effect of digitalization on firm performance in international markets. This collection of papers reviews the main factors that have been identified as having a high explanatory power at different levels.
Keywords: 330; Entrepreneurship; Internationales Management; Organisationsforschung; Welt